Macroeconomic Enablers of Sustainable Development in G20 Countries: The Role of Tourism - MISHRA, P. K.; ROUT, Himanshu B.; KUMAR, Pradip; SAXENA, Sanjeev Kumar (Theoretical and Practical Research in Economic Fields; Vol 16 No 1 (2025): TPREF Volume XVI, Issue 1(33), Spring 2025DO - 10.14505/tpref.v16.1(33).05, 2025)
The G20 countries present a congenial macroeconomic environment in terms of per capita GDP, gross fixed capital formation, labour-force participation, inflation, cross-border trade, financial sector development, and human development for the growth of travel and tourism . These countries have a strong potential for the development of travel and tourism in terms of international tourist arrivals, international tourism expenditure and international tourism receipts. As appropriately recognised by the members of G20 in 2012 for the first time, and as identified during the India’s Presidency in 2023, the potential of travel and tourism can optimally be utilized to make progress towards the SDGs by 2030. In this direction, this study is an attempt to empirically examine the impact of tourism development on sustainable development in G20 countries. The novelty of this study lies in estimating short-run and long-run effects of selected covariates on sustainable development in G20 nations in a panel framework. The results of the estimation of PMG based ARDL regression indicate a statistically significant positive contribution of the development of travel and tourism on sustainable development when macroeconomic indicators are the enablers. This finding contradicts the findings of a recent study by Destek & Aydin that tourism can be detrimental to sustainable development. Thus, the present study ushers a new direction for tourism-led sustainable development. The policy implication is that the effective and efficient implementation appropriate tourism development strategies in such a favourable macroeconomic environment can add to the progress of SDGs in G20 countries .